2017
DOI: 10.1097/md.0000000000006765
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rational emotive occupational health therapy intervention on the perceptions of organizational climate and occupational risk management practices among electronics technology employees in Nigeria

Abstract: Background:Improving employees’ perception of organizational climate, and coaching them to remain steadfast when managing occupational risks associated with their job, might have an important effect on their psychosocial wellbeing and occupational health. This study examined the effects of a rational emotive occupational health therapy intervention program on the perceptions of organizational climate and occupational risk management practices.Methods:The participants were 77 electronics technology employees in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(73 citation statements)
references
References 36 publications
(44 reference statements)
4
67
1
1
Order By: Relevance
“…In line with our finding, previous studies showed that rational emotive approach is psychotherapeutically helpful for cushioning cognitive and behavioral changes. [27,29] It was also confirmed an earlier study that REBC program gives organizational employees helpful ways of compacting occupational stress. [26,34] It also gave credence to successfully applied REBT studies [35] who showed that stress in work environment could be managed using basic principles in REBT.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In line with our finding, previous studies showed that rational emotive approach is psychotherapeutically helpful for cushioning cognitive and behavioral changes. [27,29] It was also confirmed an earlier study that REBC program gives organizational employees helpful ways of compacting occupational stress. [26,34] It also gave credence to successfully applied REBT studies [35] who showed that stress in work environment could be managed using basic principles in REBT.…”
Section: Discussionsupporting
confidence: 70%
“…Rational emotive behavior coaching manual: The REBC manual was developed by Ogbuanya et al [29] The manual aimed at providing therapeutic change in participants with severe stress that is occupationally inherent using REBT principles. REBC manual was designed to last for 3 months in that each meeting lasted for 60 minutes once a week.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Workers of America, as cited in, [ 16 ] occupational stress leads to low productivity, absenteeism, and increased rates of accidents on and off the job. Ekpenyong and Inyang [ 17 ] as reported in [ 16 ] reported that 39.25% of a group of workers in Nigeria have work-related disorders. Besides, Azodo and Ezeja [ 18 ] showed that in Nigeria, every 10 respondents showed severe occupational stress.…”
Section: Introductionmentioning
confidence: 99%
“…A computer-generated random list that was created by random allocation software was used for the allocation of participants (Saghaei, 2015). 90 participants were allocated to the experimental group and 92 participants were allocated to the waitlist control group by means of this simple randomization as in Ogbuanya et al (2017aOgbuanya et al ( , 2017b.…”
Section: Methodsmentioning
confidence: 99%